Do Foreign Currency Accounts Help Relax Credit Constraints? Evidence from Nepal. (8th September 2016) - Maskay, Nephil Matangi; Steinkamp, Sven; Westermann, Frank
Abstract: We analyse a novel bank‐level data set from Nepal, where domestic and foreign currency (FX) deposits are reported separately on the liability side of commercial bank balance sheets. In a panel regression analysis, we estimate semi‐accounting‐identities that allow us to identify the marginal sources of financing for various asset positions. We find that banks hedge against FX exposure via their sectoral lending composition: banks with a large share of FX deposits primarily lend to firms in traded‐goods sectors. Loans to non‐traded sectors are mostly financed by domestic deposits. While earlier studies have documented a positive impact of FX accounts on financial development, our analysis suggests that this does not need to imply that severely credit constrained sectors are the main beneficiaries of this process.